Analysis of Dome Home Hall theatre acoustic field - GOŁAŚ, Andrzej; SUDER-DĘBSKA, Katarzyna (Archives of Acoustics, 2009)
The modelling of compartment in simulation software enables determination of acoustic parameters' distributions in a virtual compartment. The elementary question is how much the simulations reflect the actual state in a room. Analysing the acoustics of dome-shaped compartments, i.e. for instance various basilicas, a conclusion can be drawn that the acoustics of these objects is very good. Therefore the authors decided to analyse the influence of a dome shape on acoustic parameters of the compartment.